Hyperpolarization of Amino Acids in Water Utilizing Parahydrogen on a Rhodium Nanocatalyst. Issue 47 (26th July 2019) - Kaltschnee, Lukas; Jagtap, Anil P.; McCormick, Jeffrey; Wagner, Shawn; Bouchard, Louis‐S.; Utz, Marcel; Griesinger, Christian; Glöggler, Stefan
Abstract: NMR offers many possibilities in chemical analysis, structural investigations, and medical diagnostics. Although it is broadly used, one of NMR spectroscopies main drawbacks is low sensitivity. Hyperpolarization techniques enhance NMR signals by more than four orders of magnitude allowing the design of new contrast agents. Parahydrogen induced polarization that utilizes the para ‐hydrogen's singlet state to create enhanced signals is of particular interest since it allows to produce molecular imaging agents within seconds. Herein, we present a strategy for signal enhancement of the carbonyl 13 C in amino acids by using parahydrogen, as demonstrated for glycine and alanine. Importantly, the hyperpolarization step is carried out in water and chemically unmodified canonical amino acids are obtained. Our approach thus offers a high degree of biocompatibility, which is crucial for further application. The rapid sample hyperpolarization (within seconds) may enable the continuous production of biologically useful probes, such as metabolic contrast agents or probes for structural biology. Abstract : Molecular naturism : 13 C‐hyperpolarization of unprotected natural amino acids is achieved in water, using parahydrogen induced polarization (PHIP). The strategy is promising for biological applications, since chemically unmodified amino acids are obtained directly in water, using a separable nanoparticle catalyst. Inexpensive 13 C‐hyperpolarization of natural amino acids is now at reach for biological studies (see figure).